Configuration Synthesis and Lightweight Networking of Deployable Mechanism Based on a Novel Pyramid Module - Jinwei Guo; Jianliang He; Guoxing Zhang; Yongsheng Zhao; Yundou Xu (Chinese Journal of Mechanical Engineering, 2023)
Abstract Deployable mechanism with preferable deployable performance, strong expansibility, and lightweight has attracted much attention because of their potential in aerospace. A basic deployable pyramid unit with good deployability and expandability is proposed to construct a sizeable deployable mechanism. Firstly, the basic unit folding principle and expansion method is proposed. The configuration synthesis method of adding constraint chains of spatial closed-loop mechanism is used to synthesize the basic unit. Then, the degree of freedom of the basic unit is analyzed using the screw theory and the link dismantling method. Next, the three-dimensional models of the pyramid unit, expansion unit, and array unit are established, and the folding motion simulation analysis is carried out. Based on the number of components, weight reduction rate, and deployable rate, the performance characteristics of the three types of mechanisms are described in detail. Finally, prototypes of the pyramid unit, combination unit, and expansion unit are developed to verify further the correctness of the configuration synthesis based on the pyramid. The proposed deployable mechanism provides aference for the design and application of antennas with a large aperture, high deployable rate, and lightweight. It has a good application prospect in the aerospace field.